Guideline adherence in depression outcome measurement: a retrospective cohort study from Swedish psychiatric outpatient care - El Alaoui, Samir; Jayaram-Lindström, Nitya; Bohman, Benjamin (Frontiers in Psychiatry, 2025)
BackgroundRoutine outcome measurement is a core element of measurement-based care (MBC), yet its use in everyday psychiatric practice remains limited. Even minimal follow-up assessment is often missing despite explicit clinical guideline recommendations.MethodsWe conducted a retrospective cohort study of 2431 adult outpatient episodes of depression treatment within Stockholm’s public mental health system (2020–2023). Guideline-concordant outcome measurement was defined as documentation of at least one Patient Health Questionnaire-9 (PHQ-9) or clinician-rated Montgomery–Åsberg Depression Rating Scale (MADRS) within 60 days of treatment initiation for all modalities, or within ten sessions for psychotherapy. Adherence rates were compared across antidepressant pharmacotherapy, face-to-face psychotherapy, and internet-based cognitive behavioral therapy (iCBT).ResultsAmong treatment episodes lasting ≥ 30 days (n = 2242), 28.2% included a PHQ-9 or MADRS within 60 days. Adherence was higher in psychological treatments (71.6%) than in pharmacotherapy (10.2%), χ²(1, N = 2242) = 865.14, p <.001, Cramer’s V = .62. Within psychotherapy, iCBT showed markedly greater adherence (80.1%) than traditional psychotherapy (18.0%), χ²(1, N = 656) = 146.00, p <.001, V = .47. When iCBT was excluded, adherence fell to 10.6% overall. Among psychotherapy episodes with ≥ 10 sessions (n = 482), 73.4% met the ten-session guideline, with 79.5% adherence in iCBT and 23.1% in traditional psychotherapy, χ²(1, N = 482) = 75.82, p <.001, V = .40. Younger clinicians (M = 39.8 vs. 46.8 years, p <.001) and psychologists (73%) showed higher adherence than physicians (10%) or other professions.ConclusionEven under conservative criteria, minimal outcome measurement was documented in fewer than one-third of depression treatment episodes. Adherence was particularly low in pharmacotherapy and traditional psychotherapy but substantially higher in iCBT, reflecting the advantages of automated, integrated digital workflows. These findings underscore that policy guidelines alone are insufficient; scalable implementation of MBC requires integrated digital systems, structured workflows, and targeted clinician support.